Variable, reciprocals, and fractions..
I came across another question which has just stumped me because I worked it over about 5 times and I couldn't figure out how the book got the answer. I've obtained messed up answers and none have them have been...
2x - 3(x-2)/2 = 7 - x-3/3
The thing that probably messed me up the most was the fact that I didn't know how to get the variable fractions out of the way.
I really don't remember the book covering that, therefore I sucked at it.
I did somehow try to solve it: :confused:
2(2x - 3(x-2)/2) = (7 - x-3/3)2
4x - 3x - 6 = 14 - 2x-6/3
x - 6 = 14... +6+14...
x = 20 - 2x-6/6
3(x) = (20 - 2x-6/3)3
3x = 60 - 2x - 6
8x = 54
8/8 = 54/8
So basically i'm screwing up somewhere and I don't know where but I'm not getting the right answer.